Do Bank Mergers Affect Federal Reserve Check Volume? - Joanna Stavins (Federal Reserve Bank of Boston, 2004)
The recent decline in the Federal Reserve's check volumes has received a lot of attention. Although switching to electronic payments methods and electronic checkprocessing has been credited for much of that decline, some of it could be caused by changes following bank mergers involving Federal Reserve customer banks. This paper evaluates the effect of bank mergers on Federal Reserve check-processing volumes. Using inflow-outflow and regression methods, we find that mergers between two or more Reserve Bank customers have resulted in volume losses, especially during the first quarter following the merger. On average, the estimated cumulative loss of volume during the first five post-merger quarters was 2.6 million checks. While the overall number of checks in the United States has declined during the past few years, the Federal Reserve has lost additional check-processing volume because of bank mergers.
Keywords: E58; G21; G34; 330; Bank mergers; Federal Reserve check processing; Scheck; Zentralbank; Bank; Fusion; Übernahme; Schätzung; USA